Klse Composite Index And Macroeconomic Fundamental Dynamic Interactions - YU, TEIK BENG (2005)
This thesis employs Granger causality test to investigate causal relations and dynamic interactions among Malaysia’s macroeconomic variables and Kuala Lumpur Stock Exchange Composite Index (KLCI). This research investigates the possible causal relations for different economic conditions in Malaysia by using three hundred thirty six monthly data points from January 1977 to December 2004. The macroeconomic variables being investigated are industrial production index, consumer price index, money supply measured by M1, three month fix deposit rate, Treasury bill rate and foreign exchange.